Digitalisation and productivity: A report by the ESCB expert group on productivity, innovation and technological change - Gert Bijnens; Vasco Botelho; Elisabeth Falck; Vincent Labhard; Ana Lamo; Oke Röhe; Joachim Schroth; Richard Sellner; Johannes Strobel (European Central Bank (ECB), 2024)
The productivity-enhancing effects of digitalisation have generated increased interest in the promotion of digital technologies. This report provides different estimations for euro area countries of the impact of digital uptake on productivity at firm level, showing that the adoption of digital technologies could lead to an increase in firms' productivity in the medium term. However, not all firms and sectors experience significant productivity gains from digital adoption, and not all digital technologies deliver significant productivity gains. The report highlights possible factors behind the low productivity benefits of digitalisation in euro area countries. For example, a lack of strong institutions and governance structures may help to explain why digital diffusion is slower than expected, why it is slower in some countries than others and why the expected productivity benefits from digitalisation have not been fully achieved by now. Furthermore, the report suggests that the full benefits of the digital revolution will be reaped by properly supplying skills to firms and also by investing in computerised information in low-productivity firms.
Keywords: D24; E24; E22; J24; O33; O38; C67; 330; digitalisation; productivity; institutions; human capital; complementaryinvestments